(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Wide QRS complex with left bundle branch block morphology is one of the three criteria for cardiac resynchronization therapy (CRT) in heart failure (HF) patients who do not improve on medical management. Approximately 30% of patients do not respond to CRT. This study investigates to find out to what extent the wide QRS duration correlates with the intraventricular mechanical dyssynchrony (IVMD) as measured by Tissue Doppler Imaging (TDI) echocardiography. Methods: The HF patients of dilated or ischemic cardiomyopathy with ejection fraction £35% admitted in the medical ward of Patan Hospital, Nepal from March to August 2017 were enrolled in the study. They were divided into two groups, narrow QRS duration of <120ms (Gr1) and wide QRS duration of ³120ms (Gr2). TDI was performed to measure time to peak systolic velocity of the left ventricular walls. The IVMD, defined as 60 ms (millisecond) or greater difference in time to peak velocity between any two points of the left ventricular walls, was compared in both groups. Results: There were 26 patients, 18 in group-1, and eight in Gr2.In Gr1, IVMD was observed 13/18 (72%) patients and in group-2 in 7/8 (87%) patients, (χ2 = 0.70, p = 0.403). There was no significant difference of IVMD between Gr1 and Gr2 (73±36ms vs 97±38ms, t = 1.54, p = 0.136). Conclusions: Assessment of intraventricular mechanical dyssynchrony (IVMD) by Tissue Doppler Imaging (TDI) is probably superior to QRS duration in heart failure patients.